Eventos adversos ocorridos com idosos hospitalizados - Teixeira, Cristiane Chagas (2015)
OBJECTIVE: Analyze adverse events recorded in medical records of hospitalized elderly patients. METHOD: A descriptive, cross-sectional, having as data source the records of elderly patients admitted from July 2013 to December 2013, the Surgery Unit of a teaching hospital, Midwest region of Brazil. Data collection was guided by a structured and pre-validated form and were analyzed through Statistical Package For The Social Science (SPSS), version 20.0 for Windows. The prevalence and the ranges of 95% confidence adverse events were calculated and descriptive analysis was done. To identify associated factors, chi-square test and uni and multivariate analysis were used. RESULTS: In 260 admissions, 50.4% were male, average age 68.5 years and 68.5% had comorbidities. Adverse events were identified in 531 records, defined an average of 2.04 events per admission. The types of adverse events were related to the clinical Process such as acute pain in pre and postoperative unresolved, unscheduled withdrawal and obstruction of tubular devices, failure during technical procedures, surgical dehiscence and non-drug allergic process; Medication, related to adverse reaction to medications; Blood product, related to lack of blood; Clinical management, as surgical suspension and booked exam but not performed; Hospital infection related to the surgical site, phlebitis and sepsis and Accident with the patient, such as loss and pressure ulcers. Most of the events occurred during the night shift. Damage caused to the patient were classified as mild 73.1%, 25.4% moderate, severe 0.6% and 0.9% died. The prevalence was 58.8%, indicating that hospital admissions were exposed to 153, at least one type of adverse event. The associated factor was related to length of stay for more than nine days as an independent risk variable for adverse events occurrence. CONCLUSION: The results indicate the need for initiatives by managers to modify the care practice, through educational activities, work processes improvement and better articulation between subsystems integrated into the institution, focusing on promoting quality in health services and safety culture development, especially on the elderly in hospitals.